Activation of lateral hypothalamus-projecting parabrachial neurons by intraorally delivered gustatory stimuli - Tokita, Kenichi; Armstrong, William E.; St. John, Steven J.; Boughter Jr., John D. (Frontiers in Neural Circuits, 2014)
The present study investigated a subpopulation of neurons in the mouse parabrachial nucleus (PbN), a gustatory and visceral relay area in the brainstem, that project to the lateral hypothalamus (LH). We made injections of the retrograde tracer Fluorogold (FG) into LH, resulting in fluorescent labeling of neurons located in different regions of the PbN. Mice were stimulated through an intraoral cannula with one of seven different taste stimuli, and PbN sections were processed for immunohistochemical detection of the immediate early gene c-Fos, which labels activated neurons. LH projection neurons were found in all PbN subnuclei, but in greater concentration in lateral subnuclei, including the dorsal lateral subnucleus (dl). Fos-like immunoreactivity (FLI) was observed in the PbN in a stimulus-dependent pattern, with the greatest differentiation between intraoral stimulation with sweet (0.5 M sucrose) and bitter (0.003 M quinine) compounds. In particular, sweet and umami-tasting stimuli evoked robust FLI in cells in the dl, whereas quinine evoked almost no FLI in cells in this subnucleus. Double-labeled cells were also found in the greatest quantity in the dl. Overall, these results support the hypothesis that the dl contains direct a projection to the LH that is activated preferentially by appetitive compounds; this projection may be mediated by taste and/or postingestive mechanisms.